Exosomes in cancer immunoediting and immunotherapy - Yarong Zhao; Luotong Liu; Rongze Sun; Guilin Cui; Shuyu Guo; Songren Han; Ziwei Li; Tian Bai; Lesheng Teng (Asian Journal of Pharmaceutical Sciences, 2022)
As an important means of communication among cells, exosomes are being studied more and more widely, especially in the context of cancer immunotherapy. In the phase of tumor immunoediting, exosomes derived from tumor cells and different immune cells have complex and changeable physiological functions, because they carry different proteins and nucleic acid from the source cells. Based on the role of exosomes in the communication between different cells, cancer treatment methods are also under continuous research. This review briefly introduces the molecular composition of exosomes, which is closely related to their secretion mechanism. Subsequently, the role of exosomes encapsulating different information molecules is summarized. The role of exosomes in the three phases of tumor immunoediting is introduced in detail, and the relevant literature of exosomes in the tumor immune microenvironment is summarized by using a novel framework for extracting relevant documents. Finally, it summarizes the various exosome-based immunotherapies currently proposed, as well as the challenges and future prospects of exosomes in tumor immunotherapy.